Fifth International Congress on Peer Review in Biomedical Publication - travel scholarship report - Isabel CF da Cruz (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2005)
The travel fellowship offered by the Congress on Peer Review offered an oportunity for developing an editor career. This scholarship enable the OBJN´s editor to study the organization of a scientific journal and to look at new techniques for publishing. This unique opportunity projected also the Online Brazilian Journal of Nursing in the international arena of Biomedical Editors.